Iterative Algorithms for New General Systems of Set-Valued Variational Inclusions Involving (A,η)-Maximal Relaxed Monotone Operators - Ting-jian Xiong; Heng-you Lan (Journal of Applied Mathematics)
We introduce and study a class of new general systems of set-valued variational inclusions involving (A,η)-maximal relaxed monotone operators in Hilbert spaces. By using the general resolvent operator technique associated with (A,η)-maximal relaxed monotone operators, we construct some new iterative algorithms for finding approximation solutions to the general system of set-valued variational inclusion problem and prove the convergence of this algorithm. Our results improve and extend some known results.